CHANGING APPROACHES TO ANALYSIS IN LITERARY-CRITICAL ESSAYS - Aslbek Ergashev (Western European Studies, 2024)
The analysis of a literary critical essay should be viewed through the prism of its communicative function. It is important to note that in modern times, the text no longer reflects only the product of thought and the event sealed in written form, it draws attention to the interactions between the participants of communication, even if they are far from each other. Therefore, researching the essay as a communicative text is an important aspect.
Keywords: Look and someone; the method of speech